1950
DOI: 10.1021/ac60048a028
|View full text |Cite
|
Sign up to set email alerts
|

Coulometric Titration of 8-Quinolinol

Abstract: collected in proximity tu dustproducing processes, wch as those carried on in the ore preparation department, had a nirdian size (2.2 microns) greater than those in the maintenanre liuilding (1.1 microns) which is more remote from the major w u r w c of dust pollution. This gr:itl:ition i b logic-a1 nL:CEI\-E." hlarch 1:i, 1930. This rirojccr was supported by a cancer control grant from t h e Hariford Forks, General Elertrir Company, Rirhland, R'ash.4 microtitration of 8-quiriolinol with electrolytically gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1952
1952
1969
1969

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…More recently the coulometric method of measuring the current consumed in the titration has been replaced by the use of a constant-current generator (3,18), and the calculations are based on the time during which this known current is applied to the cell, so that one might more properly speak of a "chronometric" titration (SI). At the same time amperometric (S, 8, 13, 16, 19, SS) and potentiometric (4, 6, 7, 9, 17, SI) methods for the detection of the end point have found wide application.…”
supporting
confidence: 93%
“…More recently the coulometric method of measuring the current consumed in the titration has been replaced by the use of a constant-current generator (3,18), and the calculations are based on the time during which this known current is applied to the cell, so that one might more properly speak of a "chronometric" titration (SI). At the same time amperometric (S, 8, 13, 16, 19, SS) and potentiometric (4, 6, 7, 9, 17, SI) methods for the detection of the end point have found wide application.…”
supporting
confidence: 93%
“…The published (ethylenedinitrilo)tetraacetate titration methods (1) for the determination of magnesium, in which magnesium is determined by difference of two titrations (5), are not sufficiently accurate for magnesium oxide levels as low as 0.05% in commercial calcium phosphates and a few tenths of a per cent in commercial lime. Phosphate interference in the EDTA titration is overcome by precipitation of the phosphate with ferric ions at a pH low enough to prevent precipitation of magnesium (5).…”
Section: Resultsmentioning
confidence: 99%
“…As the striking enhancement of the color obtained with the molybdate reagent and silicate in the presence of TCA suggested that this procedure might be analytically useful, silicate was determined with both the system used for phosphate (1) and the method devised for silicate (2) with TCA present. Also, the concentration of the sulfuric acid was varied to determine the effect of intermediate concentrations.…”
mentioning
confidence: 99%
“…Servo mechanical systems have since been devised (e.g., 3,4) which give currents constant to better than 0.01% over long periods, although their response times are not fast. A number of electronic current regulators using vacuum tubes have also been described (e.g., [5][6][7][8][9] generally involving dc amplifiers with feedback. A common method in present electrochemical practice is to place the electrolytic cell in the feedback loop of a standard operational amplifier unit (see Fig.…”
mentioning
confidence: 99%